Model to Evaluate Customer Satisfaction During the Product Life Cycle - Ioana Alina Mitrache; Irina Severin; Elena Lascu; Florin Stinga (Communications of International Proceedings, 2020)
According to the market evolution, the biggest companies express the desire to create quality through satisfaction, while building a management of a real customer culture that use customer satisfaction inside the business model. The case study presents how the customer satisfaction level influences the developing of a new product through his life cycle, in an Automotive Company proposing a model of evaluation. The purpose of the article is to highlight the influence of the customer satisfaction on each step necessary for product developing by choosing appropriate methods for customer satisfaction evaluation. Following the four stages of the product life cycle chosen as reference: Exploring, Development, Launching and Post-Launching, through the proposed model, it will be revealed how the customer decides starting from the beginning the segment and the main characteristics for a new vehicle. The model may be extended to other industries.
Keywords: Customer Satisfaction Level; Customer Feedback; Survey Methodology.